PENGARUH GLOBALISASI TERHADAP POLITIK HUKUM BERBASIS PERLINDUNGAN HAM DI INDONESIA - Shinta Dewi Rismawati, Shinta Dewi Rismawati (Jurnal Hukum Islam, 2012)
In the Era of Globalization, human rights has become one of the international political commodities that can be used by international agencies and foreign countries to pressure the regime of a nation. Therefore, Indonesian government as a part of global communities has to establish a legal politics (legal policy) that promotes on the protection of human rights. It is a strategic tool that can be applied for coloring, characterizing, and forming the legal system. This article tries to see the concrete manifestation of the legal politics (legal policy) which has been presented in the form of legal institutions that provide recognition and protection of human rights for the people of Indonesia.